Abstracts of the 2015 CSBBCS Annual Meeting: Résumés du congrès annuel 2015 de la SCCCSC. (Canadian Journal of Experimental Psychology / Revue Canadienne de Psychologie Expérimentale, 2015)
Abstracts of the 2015 CSBBCS Annual Meeting are presented including "Sex Differences While Viewing an Erotic Video," "Enhanced Local Processing in Autism: Evidence from Eye-tracking Dynamic Events," and "Low Voice Pitch Predicts Sociosexual Attitude in Women."